THE FINANCIAL PERFORMANCE APPRAISAL OF SELECTED PRIVATE SECTOR BANKS IN INDIA: AN EMPIRICAL EVIDENCE - Bhatt, Vyomkesh; Arora, Mehak (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Banking Institutions work as a strong catalyst for maintaining a sound financial system in a country. Banking Institutions act as a financial intermediary in the financial system of the country. In India the banking sector comprises of public sector banks, private sector banks, regional rural banks and foreign banks mainly. The present study focuses upon the financial performance of selected private banks – HDFC Bank, ICICI Bank, Axis Bank, Kotak Mahindra Bank, Induslnd Bank and Federal Bank for a period of 11 years from 2011 to 2021. The study is based upon secondary data. The financial performance is analyzed from the viewpoint of return ratio, profitability position, efficiency and market prospect. The study depicts that all the selected bank except for Federal Bank and Induslnd Bank performance is at satisfactory level. Descriptive statistics is used along with one way ANOVA test which determined that there is significant difference in the variables of selected private banks.